CRISPR-Cas9 Knock-In of T513M and G41S Mutations in the Murine β–Galactosyl-Ceramidase Gene Re-capitulates Early-Onset and Adult-Onset Forms of Krabbe Disease - Rebiai, Rima; Rue, Emily; Zaldua, Steve; Nguyen, Duc; Scesa, Giuseppe; Jastrzebski, Martin; Foster, Robert; Wang, Bin; Jiang, Xuntian; Tai, Leon; Brady, Scott T.; van Breemen, Richard; et al. (Frontiers in Molecular Neuroscience, 2022)
Krabbe Disease (KD) is a lysosomal storage disorder characterized by the genetic deficiency of the lysosomal enzyme β-galactosyl-ceramidase (GALC). Deficit or a reduction in the activity of the GALC enzyme has been correlated with the progressive accumulation of the sphingolipid metabolite psychosine, which leads to local disruption in lipid raft architecture, diffuse demyelination, astrogliosis, and globoid cell formation. The twitcher mouse, the most used animal model, has a nonsense mutation, which limits the study of how different mutations impact the processing and activity of GALC enzyme. To partially address this, we generated two new transgenic mouse models carrying point mutations frequently found in infantile and adult forms of KD. Using CRISPR-Cas9 gene editing, point mutations T513M (infantile) and G41S (adult) were introduced in the murine GALC gene and stable founders were generated. We show that GALCT513M/T513M mice are short lived, have the greatest decrease in GALC activity, have sharp increases of psychosine, and rapidly progress into a severe and lethal neurological phenotype. In contrast, GALCG41S/G41S mice have normal lifespan, modest decreases of GALC, and minimal psychosine accumulation, but develop adult mild inflammatory demyelination and slight declines in coordination, motor skills, and memory. These two novel transgenic lines offer the possibility to study the mechanisms by which two distinct GALC mutations affect the trafficking of mutated GALC and modify phenotypic manifestations in early- vs adult-onset KD.